1997
DOI: 10.1111/j.1365-2222.1997.tb01256.x
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial and cutaneous responses in atopic dermatitis patients after allergen inhalation challenge

Abstract: We conclude that allergen inhalation challenge causes a flare up of the skin lesions in atopic dermatitis patients. This was more prominent in atopic dermatitis patients who already suffered from an IgE-mediated allergic inflammation in the lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Bronchial hyperresponsiveness to methacholine in patients with AD revealed a more prominent flare-up of skin symptoms in those patients with AD who already had IgE-mediated inflammation of the lung. 26 Tupker et al 24 also observed that all patients with AD with a skin reaction on bronchial exposure to house dust mite had a history of asthma.…”
Section: Discussionmentioning
confidence: 94%
“…Bronchial hyperresponsiveness to methacholine in patients with AD revealed a more prominent flare-up of skin symptoms in those patients with AD who already had IgE-mediated inflammation of the lung. 26 Tupker et al 24 also observed that all patients with AD with a skin reaction on bronchial exposure to house dust mite had a history of asthma.…”
Section: Discussionmentioning
confidence: 94%
“…Among patients being treated for eczema, allergen inhalation challenge caused a flare-up of skin lesions in patients, which was worse in those with allergic asthma. 16 The same authors examined early and late asthmatic responses after allergen inhalation challenge in groups of patients with varying degrees of atopic dermatitis and asthma. 17 After bronchial challenge, patients with atopic dermatitis and without asthma demonstrated increased bronchial responsiveness and early asthmatic responses, suggesting a latent predisposition to bronchial asthma.…”
Section: Systemic Consequences Outside the Respiratory Systemmentioning
confidence: 98%
“…In 1997, Brinkman et al showed that dustmite allergen inhalation challenge can cause a flare up of skin lesions in patients with pre-existing atopic dermatitis and dust-mite sensitization. 25 The worsening in the clinical score for dermatitis occurred around 24 hours after the inhalation challenge and no acute cutaneous symptoms were noted. Interestingly, the effect of the inhalation challenge on the skin was more pronounced in the subjects who also had asthma, as opposed to those who only had allergic rhinitis.…”
Section: Further Support For the Systemic Propagation Of Localized Almentioning
confidence: 99%